Potential quimioprotetor do DIM (3, 3' - Di-indolil-metano) e da Genisteína em linhagens de células tumorais prostáticas humanas LNCaP e PC-3 expostas ao Bisfenol A - Pinho, Cristiane Figueiredo [UNESP] (2015)
The prostate cancer initiation and progression present hormonal basis and this is mainly related to changes involving estrogens and androgens inherent aging process, where there is an increment of estrogens levels relative to androgens. Nowadays, Bisphenol A (BPA) is the most studied xenoestrogen and its estrogenic activity has attracted attention for its wide dispersion in the environment. Thus, this compound could contribute to the increased incidence, aggressiveness and metastatic ability of prostate tumors. Moreover, the chemoprotection with dietary phytochemicals is associated with a reduction in the incidence and progression of different cancers, decrease inflammatory processes and oxidative stress caused by potentially harmful substances. Therefore, this study aimed to evaluate the effects of phytochemicals 3,3 '-Di-indolyl-methane (DIM) and Genistein (Gen) isolated and/or associated to prostatic tumor cells exposed to BPA. For this purpose, LNCaP and PC-3 cells were cultured and exposed, for 96 hours, to the treatments C (control), B (BPA10nM/L), BD (BPA 10nM/L + DIM 25μM/L), BG (BPA 10nM/L + Gen 25μM/L) e BDG (BPA 10nM/L + DIM 25μM/L + Gen 25μM/L); which doses were established by cell viability assay. Subsequently, the cells were subjected to protein extraction for Western Blotting in order to analyze proteins involved in survival, proliferation, cell death, hormonal modulation and oxidative stress processes. The results showed that BD, BG and BDG treatments, in LNCaP cells, were able to down-regulate AR expression. About the ERK1/2 proteins in PC-3 lineage, B caused an increase of expression, while BDG was responsible for a decrease. However, in LNCaP, reducing the expression of MAPK was due to BG treatment. For the JNK1/2 protein, B had ability to down-regulate its expression and, on the other hand, phytochemicals from 3 treatments (BD, BG and BDG), increasing its expression in LNCaP. For the same cell lineage, the ERα ...